2021
DOI: 10.3390/molecules26113126
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Fruit and Vegetable Whey Beverages and Fruit and Vegetable Mousses

Abstract: The study assesses the antioxidant activity, total phenolic content, total flavonoids content and lipophilic pigments (β-carotene, chlorophyll a, chlorophyll b) content in homemade and marketed fruit and vegetable whey beverages and fruit and vegetable mousses. All of the tests were performed using spectrophotometric methods. The highest polyphenol content was found in the homemade green whey beverage W1G (541.95 mg/100 g) and the lowest in the market green whey beverage W2G (46.18 mg/100 g). In the fruit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…It has been shown that combination of whey with additional antioxidant ingredients (vitamin B12, astaxanthin and plant extracts) improves the bioactivity of the formulated beverages [ 49 ], and that values of antioxidant activity in whey-based drinks added with fruit and vegetables are positively correlated with the polyphenol content [ 17 ]. Results of the present assay are comparable with those found for homemade beverages prepared with 50% whey and with fruits (pear, cherry and banana) and vegetables (carrot and parsley) added, in which DPPH and ORAC values were around 0.78 and 0.71 mM trolox Eq./kg, respectively [ 17 ]. Therefore, it seems clear that antioxidant properties of the intact Colada were due, in addition to the whey proteins, to antioxidant compounds, especially polyphenols, provided by barley and Maracuyá [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that combination of whey with additional antioxidant ingredients (vitamin B12, astaxanthin and plant extracts) improves the bioactivity of the formulated beverages [ 49 ], and that values of antioxidant activity in whey-based drinks added with fruit and vegetables are positively correlated with the polyphenol content [ 17 ]. Results of the present assay are comparable with those found for homemade beverages prepared with 50% whey and with fruits (pear, cherry and banana) and vegetables (carrot and parsley) added, in which DPPH and ORAC values were around 0.78 and 0.71 mM trolox Eq./kg, respectively [ 17 ]. Therefore, it seems clear that antioxidant properties of the intact Colada were due, in addition to the whey proteins, to antioxidant compounds, especially polyphenols, provided by barley and Maracuyá [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the large increase found in TPC of the Colada BF could be due to the different chemical structures of the existing polyphenols and their biotransformation during digestive conditions. In addition, the fact that the Folin–Ciocalteu reagent, used for the determination of polyphenolic compounds, could react with amino acids from whey digest leading to overestimation of results [ 17 ], cannot be discarded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carotenoids are a diverse group of colorful pigments that produce the yellow, orange and red colors in many fruits, vegetables and flowers [ 1 ]. Carotenoids and their derivatives have diverse biological functions in plant growth, development and reproduction [ 2 ].…”
Section: Introductionmentioning
confidence: 99%